Desenvolvimento econômico dos municípios paranaenses: análise a partir do índice FIRJAN de Desenvolvimento Municipal (IFDM) para o período de 2005 a 2013 - Dalchiavon, Eloisa Carla (2017)
This study has for general objective to analyze the economic development, measured to IFDM, of the municipality of the state of Parana in the period from 2005 to 2013.The specific objectives are: present the evolution of the IFDM of the municipality of the state of Parana, for the state and geographic mesoregions; analyze the spatial distribution of the developed of the state of Parana in the period from 2005 to 2013 and check the composition of the job in the period, of the mesoregions. For the objectives proposed draw on the descriptive analysis of the data in relation the IFDM, the Exploratory Spatial Data Analysis (ESDA), seeking to view how is spatially distributed the development of Parana, and the method of analyze shiftshare to study the employment performance in the regions and sectors of economic activities. The results found for the descriptive analysis show that the economic development of the states of Parana occur different way between regions, stand out the mesoregions North Central and West, that had greater number of municipalities classified with high development (IFDM general) in 2013. In contrast, the mesoregion Central South didn't present municipalities with high IFDM general, in both the years. The results of the ESDA indicate the existence of the autocorrelation spatial positive in the data, in other words, there is similarity between the values of the IFDM general of the municipalities and their spatial localization. The maps of cluster LISA indicated the existence, in 2005, of the three clusters high-high located in the regions: North Central, Northwest and west of the state, and two clusters low-low located in the regions: Middle Western ,North Central, Middle Oriental and Middle South. In 2013, there was a increase in the number of the significant clusters, and theses lie longer distributed than in 2005. Were indentified four clusters high-high, that belong the regions North Central, Northwest, West and Southwest, and three clusters low-low belong the regions: Middle South, Middle Western, Middle Oriental, North Central, North Pioneer and Southeast. In relation the analyze shift-share of employment of the state, the number of jobs of Parana, from 2005 to 2013, increased 47,98%. It was verified that the three sectors that presented the highest employment growth in the state were: Construction industry; Footwear Industry and Mechanical Industry. In regional terms, the regions Southwest, West, Northwest and North Central stand out with the percentage change of increase of employment greater than state. The group of analysis realized allow to infer the regions that in relation of IFDM general of municipalities are that present clusters of development significant high-high, in other words, the municipalities these regions present high value of IFDM general and they are surrounded by municipalities with high value too. Similarly, the regions with the highest employment growth, according to shift-share analysis, they are that didn't have improve IFDM general and identification of clusters of development high-high.